2011
DOI: 10.3168/jds.2010-3505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential oils on rumen fermentation, milk production, and feeding behavior in lactating dairy cows

Abstract: Seven ruminally cannulated lactating Holstein dairy cows were used in an incomplete Latin rectangle design to assess the effects of 2 commercial essential oil (EO) products on rumen fermentation, milk production, and feeding behavior. Cows were fed a total mixed ration with a 42:58 forage:concentrate ratio (DM basis). Treatments included addition of 0.5 g/d of CE Lo (85 mg of cinnamaldehyde and 140 mg of eugenol), 10 g/d of CE Hi (1,700 mg of cinnamaldehyde and 2,800 mg of eugenol), 0.25 g/d of CAP (50mg of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
73
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 25 publications
18
73
3
5
Order By: Relevance
“…The findings of the present study for ruminal pH were in line with previous researches in sheep (Chaves et al, 2008a;b), dairy cows (Yang et al, 2007; Kung et al, 2008; Tager and Krause., 2011), and beef cattle (Cardozo et al, 2006; Fandino et al, 2008; Meyer et al, 2009; Yang et al, 2010a;c) that found no effect of EO on pH. It should be noted, that although ruminal pH was unaffected by EO supplementation, the mean ruminal pH of the bull calves in this research was lower (5.87 to 5.98) compared to results (6.08 to 6.52) of Devant et al (2007); which examined effects of plant extract supplementation in young Holstein bulls who consumed high concentrate diets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study for ruminal pH were in line with previous researches in sheep (Chaves et al, 2008a;b), dairy cows (Yang et al, 2007; Kung et al, 2008; Tager and Krause., 2011), and beef cattle (Cardozo et al, 2006; Fandino et al, 2008; Meyer et al, 2009; Yang et al, 2010a;c) that found no effect of EO on pH. It should be noted, that although ruminal pH was unaffected by EO supplementation, the mean ruminal pH of the bull calves in this research was lower (5.87 to 5.98) compared to results (6.08 to 6.52) of Devant et al (2007); which examined effects of plant extract supplementation in young Holstein bulls who consumed high concentrate diets.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast recently Yang et al (2010b) reported that dietary supplementation with cinnamaldehyde increased DMI of feedlot cattle in the early wk of the fattening period, although, cinnamaldehyde had no effect on DMI after 4 wk of the experiment. Lack of effect of EO on DMI has been reported (Benchaar et al, 2007; Yang et al, 2007; Tassoul et al, 2009; Tager and Krause, 2011), but also other studies showed that EO can decrease DMI (Cardozo et al, 2006; Fandino et al, 2008). In some of studies, depression of DMI in cattle supplemented with EO might be related to palatability problems, proposing that the EO require to be encapsulated to overcome this problem (Calsamiglia et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Overall, rumen fermentation parameters were not affected by CAP in the current experiment, although a slight decrease (P = 0.06) in pH was observed. These results are consistent with those reported by Tager and Krause (2011), in which ruminal ammonia and VFA concentrations were not affected by 250 mg/d of a Capsicum product in lactating dairy cows. Others, however, have reported decreased pH and acetate concentration and increased ammonia concentration in the rumen of beef cattle supplemented with encapsulated Capsicum oleoresin (Rodríguez-Prado et al, 2012).…”
supporting
confidence: 95%
“…For example, the amount of Capsicum oleoresin used in the study of Rodríguez-Prado et al (2012) was 2.5 to 10.6 mg/kg of DMI, whereas application rate of Capsicum oleoresin was 1.8 to 7.5 mg/kg of DMI in the current study. Tager and Krause (2011) also reported no effect of Capsicum on DMI in dairy cows. The combination of dietary nutrient supplies and quadratic increases of milk, 4% FCM, and ECM yields with CAP supplementation in the current experiment resulted in negative NE L balances (−0.9 Mcal/d) for both C250 and C500 treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Some in vitro studies both of long and short term and in vivo studies reported that EO did not affect NDF digestibility as noted in our results (Benchaar et al, 2006;Tassoul & Shaver, 2009;Santos et al, 2010;Tager & Krause, 2011). However, Fernandez et al (1997) observed that sheep given EO from 50 to 1 000 mg /day caused a marked inhibition in fiber digestion in the rumen, which may be due to the selective effect of EO on the rumen microbial population (McIntosh et al, 2003).…”
Section: In Vivo Experimentscontrasting
confidence: 53%